ANALISIS PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) DI SENTRA BERMAIN PERAN - Resna Rizki Pujawati; Dian Surya Aprilyanti; Siti Khosiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the age range of 4-6 years, children begin to develop social skills through interaction in the school environment. Social studies (IPS) learning in early childhood education is not presented explicitly as an independent subject but is integrated into various learning activities, one of which is role-play. This study aims to determine how social studies learning is implemented in the role-play center and to identify the branches of social science that emerge within it. A descriptive qualitative method with a case study approach was used. Data were collected through structured observation, structured interviews, field notes, and documentation, then analyzed using the Miles and Huberman interactive model, with credibility established through prolonged engagement, persistence, source and technique triangulation, member checks, negative case analysis, and referential material. The subjects were the school principal, teachers, and children of Group B at Pembina Cibeber State Kindergarten, Cilegon City, Banten. The results show that social studies learning has been implemented in an integrated manner through three stages: planning, implementation, and evaluation, although its application is not yet evenly distributed across all learning themes. All branches of social studies-history, geography, economics, sociology, and anthropology-emerged contextually through role-play activities such as buying and selling, introducing locations and historical figures, cooperation, conflict resolution, and the introduction of local culture and traditions.